MANAJEMEN RESIKO PROYEK: SUATU KAJIAN TEORITIS - Prapti, Meniek Srining (J@ti Undip : Jurnal Teknik Industri, 2007)
Project is illegitimate activity, complex, and limited by time, cost, and specification which have been determined. Complexity and uncertainty of project enable the happening of risk and conflict emerge from within and outside of the project.Â  Project risk eliminated by applying project risk management, so project performance can be reached.Â  Organization have to able to identity and determine the criteria of efficacy of project performance